How psychological empowerment impacts task performance: The mediation role of work engagement and moderating role of age - Juyumaya, Jesus (Frontiers in Psychology, 2022)
This paper presents a mediation–moderated model of the relationship between psychological empowerment, work engagement, age, and task performance. I seek to provide a more nuanced understanding of the mediating role of work engagement in the positive effect of psychological empowerment on task performance. Further, I explore employee age as a moderating factor in this mediation. I used online surveys among a sample of Latin American textile industry employees to capture individual perceptions about psychological empowerment, work engagement, and task performance. I modeled a mediation–moderated model using Hayes’ Process macro. The results confirm that the positive impact of employee psychological empowerment on task performance is partially mediated by work engagement. In addition, age was a significant moderator of the mediation effect. This study expands knowledge about how the psychological empowerment–work engagement relationship can predict task performance, including age as a boundary condition. Following the Job Demands–Resources theory, I also prove that conceptualizing psychological empowerment as a job resource can benefit the integration of psychological empowerment and the work engagement stream of research. Moreover, the findings may help human resources management researchers and practitioners acknowledge contextual differences in understanding the combined effects of psychological empowerment and work engagement. For instance, textile industry human resources managers can develop specific age–based human resource systems that empower and engages employees from emerging economies.